TUJUH BELAS TAHUN STUDI AKUNTANSI ZAKAT DI INDONESIA: SEBUAH REVIU SISTEMATIK DAN SARAN UNTUK RISET DI MASA MENDATANG - Hafiez Sofyani (Media Riset Akuntansi, Auditing & Informasi, 2019)
Roughly 17 years have passed since the first article on zakat accounting was written by Harahap and Yusuf (2002). Until 2019 today, the average accounting zakat articles published in accredited journals ranking 2 and 3 are only 1.53 per year. This indicates that attention to the issue of accounting for zakat by accounting academics is low. Various problems related to zakat accounting research are presented in this paper, starting from the shallowness of the study, there was no connection between one research with other research, and monotonous topics which have no follow-up on research design that should be more in-depth. Many papers also did not really present practical and theoretical contributions. Various research paradigms which are actually very valuable to be employed in zakat accounting research have also not been explored further. Departing from the various problems, this paper tries to provide direction for future research regarding zakat accounting issue. This paper is a systematic review of published research as well as developments in academic and practices issues in the field related to zakat accounting and Zakat Management Organization (OPZ). Review results offers three points of improvement for future studies, namely the proposal of several contemporary issues/topics that need to be investigated, the research paradigm recommended to be applied, and theories or concepts that need to be tested related to research on zakat accounting.